2019
DOI: 10.1111/1365-2664.13349
|View full text |Cite
|
Sign up to set email alerts
|

Late flowering time enhances insect pollination of turnip rape

Abstract: 1. Ecological intensification has been proposed as a strategy to mitigate the impacts of conventional intensive land use on pollinators and insect pollination. However, research has concentrated on the effects of land management on pollinator abundance and diversity, while studies directly measuring pollination services are still lacking for many crops and regions.2. This study examines the effects of landscape heterogeneity, pesticide use intensity and flowering time on insect pollination of turnip rape Brass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…However, observational squares are more practical in monitoring pollinator visitation to crop flowers, and they also allow linking pollinator visits to crop yield. The effects of pollinator visits on turnip rape yield in the same study system were reported by Toivonen et al (2019): The number of seeds per silique increased with increasing number of flower visits, indicating enhanced crop pollination, whereas species richness of pollinators had no yield effect.…”
Section: Pollinator Monitoringsupporting
confidence: 57%
“…However, observational squares are more practical in monitoring pollinator visitation to crop flowers, and they also allow linking pollinator visits to crop yield. The effects of pollinator visits on turnip rape yield in the same study system were reported by Toivonen et al (2019): The number of seeds per silique increased with increasing number of flower visits, indicating enhanced crop pollination, whereas species richness of pollinators had no yield effect.…”
Section: Pollinator Monitoringsupporting
confidence: 57%
“…oleifera) and turnip rape (Brassica rapa subsp. oleifera) are examples of crops that strongly attract honeybees and wild bees but also suffer from harmful pests such as common pollen beetle (Brassicogethes aeneus) that may destroy the entire yield if not controlled (e.g., Toivonen et al 2019;Lindstöm et al, 2017). Commonly used insecticides in the cultivation of oilseed brassicas include pyrethroids taufluvalinate, esfenvalerate, and lambda-cyhalothrin, as well as Responsible Editor: Philippe Garrigues * Lotta Kaila lotta.kaila@helsinki.fi; ext.lotta.kaila@luke.fi Extended author information available on the last page of the article the nenonicotinoid thiacloprid, which all interfere with the insect nerve system (Davies et al 2007;Tomizawa & Casida 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several publications in our analysis were conducted to measure differences in pollination service at different locations by comparing the yield of open‐pollinated plants with control plants enclosed in cages at each location (e.g. Perrot et al, 2018; Toivonen et al, 2019; Zou et al, 2017). Based on previous research (Garibaldi, Steffan‐Dewenter, et al, 2011; Lázaro & Alomar, 2019), we hypothesised that differences (instability) in pollination service between locations would make yield less stable in these open pollination experiments, in comparison to experiments where pollinator activity was maximised by introduction of pollinating insects or hand‐pollination inside cages (e.g.…”
Section: Methodsmentioning
confidence: 99%